Immunological studies in a patient with ulcerative colitis and sarcoidosis. Issue 7 (July 1971) - Watson, David W.; Friedman, Harold M.; Quigley, Alicia
Abstract : This report describes a patient with both ulcerative colitis and sarcoidosis. This association is of interest because of the anergy for cellular immunity which was characteristic of the sarcoidosis and the cytotoxic effect of the patient's lymphocytes for allogenic colon epithelial cells which characterized the ulcerative colitis. This concordance of immunological findings suggests that the cytotoxic effect may have a basis other than cellular immunity.